Coxiella burnetii in wild birds from Europe - Loureiro, Filipa; Cardoso, LuÃs; Matos, Ana; Matos, Manuela; Coelho, Ana Cláudia (Journal of Advanced Veterinary Research, 2024)
Coxiella burnetii is a highly infectious bacterium responsible for causing Q fever, an emerging public health problem of global concern and the cause of severe economic losses in livestock farming. Many species can be asymptomatic carriers and shed this bacterium in various secretions and excreta. Humans can acquire the infection mainly through environmental contamination due to bacterial shedding of infected animals, and through tick-borne or foodborne transmissions. If this agent is aerosolized, it is considered a potential biological weapon. Advanced molecular and serological diagnostic techniques for Q fever over the last decade have made it possible to detect clinical cases and carry out population screening effectively. There needs to be more research on C. burnetii control in wildlife despite the increasing evidence that wildlife is a source of C. burnetii for both domestic animals and humans. Birds can transmit this pathogen directly or indirectly to other animals or humans, but data about the spreading of C. burnetii in avian populations still need to be available. The present work aimed to revise the literature about the involvement of wild birds in the epidemiology of Q fever in Europe. Reports of this pathogenic agent in wild birds in European countries since 2007 were considered.